Administrative Creativity and its Relationship to Job Performance among Administrative Leaders in the Iraqi Faculties of Physical Education and Sports Sciences - Hayder Flayyih, Bahaa; Farhan Majhool, Mazin; Aswad Layikh, Khalid (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to identify the correlation of administrative creativity among the administrative leaders in the Faculty of Physical Education and Sports Sciences (FPESS) and to identify the correlation of job performance among the administrative leaders in the FPESS, as well as to identify the relationship Between the administrative creativity and the performance of the administrative leaders in the Iraqi FPESS, the research problem lies in answering the following questions: first, what is the correlation of administrative creativity among the administrative leaders in the FPESS, and second, what is the correlation of job performance among the administrative leaders in the FPESS. The researcher followed the analytical descriptive research approach, which depends on the collection of facts and then comparing analyzing and interpreting them down to the conclusions that provide researchers with real information about the phenomena studied and influential in the research subject. The researchers identified the research community of administrative leaders in the faculties of physical education and sports sciences which was 90 and the researchers chose 84 study sample after excluding the exploratory experiment samples. The researchers concluded that the administrative leaders in the faculties of physical education and sports sciences in Iraq enjoy a high level of administrative creativity and a high level of job performance and the researchers recommended strengthening the administrative creativity level enjoyed by the administrative leaders in various ways and in all fields in order to maintain this level of creativity in administrative job performance.